THE MAIN TYPES OF CAR ENGINES AND THE WORKING CYCLE (Scientific journal of the Fergana State University, 2024)
In modern cars, internal combustion engines are mainly common. Internal combustion engines by design aredivided into piston and rotary. Reciprocating internal combustion engines are mainly used in cars.As a result of thecombustion of fuel, the pressure created due to the expansion of the gas pushes the piston in a linear direction back andforth, thus driving the crankshaft in motion. The internal engine requires air and a combustible mixture to operate.